EVALUASI KEBIJAKAN PEMENUHAN HAK PEKERJAAN SEKTOR FORMAL BAGI PENYANDANG DISABILITAS DI LINGKUNGAN PEMERINTAH KOTA BANDUNG - Cut Novi Syahfitri; Muh. Ilham; Deti Mulyati; M. Zubakhrum B. Tjenreng (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
This research is focused on evaluating the implementation policy of persons with disabilities in fulfilling formal sector employment rights in the city of Bandung based on William N. Dunn's evaluation theory which includes 6 (six) criteria, namely effectiveness, efficiency, adequacy, equity, responsiveness, accuracy. This study aims to analyze the evaluation of policies for the implementation of protection of people with disabilities in the fulfillment of formal sector employment rights in Bandung City and provide policy recommendations and policy implementation models related to the implementation of protection of persons with disabilities in the fulfillment of formal sector employment rights in Bandung City. The study used this using exploratory qualitative methods with an inductive approach. Interviews, documentary, observational, and triangulation techniques are the data collection techniques used in this study. The results of this study can be concluded that the evaluation of policies for the implementation of persons with disabilities in fulfilling the right to work in the formal sector in Bandung City has not been optimal, this can be seen that the policies that have been running since its publication until this study was made have not met the six criteria, namely effectiveness, efficiency, adequacy, similarity, responsiveness, and accuracy. Based on the analysis of these results, this study proposes policy recommendations, namely increasing government collaboration and integrity, strengthening the role of the government, accelerating the revision of West Java Provincial Regulations related to persons with disabilities which will later be elaborated through the Bandung Mayor Regulation, synchronization of precise and accurate data and information, and preparation of policies supporting the West Java Provincial Government Regional Regulation on Persons Disability. The policy implementation model is leadership, communication, policy substance, supervision, and resources.